THE IMPORTANCE OF TEACHING FOREIGN LANGUAGES IN MODERN UZBEKISTAN (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Foreign language education in modern Uzbekistan has become a key direction of educational reform and international integration. The country’s government has taken major steps toward improving the quality of teaching, developing teachers’ professional skills, and introducing international standards of language assessment. The modernization of teaching methods, digital transformation, and communicative approaches have significantly influenced how foreign languages are taught across all levels of education. This article examines the evolution, current trends, and future prospects of foreign language teaching in Uzbekistan, highlighting the impact of policy reforms, technological progress, and teacher training programs.